THE MULTIPLE POSSIBILITIES OF OPTIONS MARKET IN JORDAN - Alwedyan, Adnan Mohamad Issa (European Scientific Journal, ESJ, 2012)
This study tried to answer of this question :Are there possibilities to apply the options market on Jordan market as hedging risk technique .The study used questionnaire method that targeted common and professional investors who deal in Amman stock market. The results revealed that investors does not like the option market to apply in Jordan market, which refer to following reasons: 1- high risks resulting from using option market. 2- Lack of the necessary expertise to develop this market to match with \the possibilities of the Jordanian market. 3- the weakness of Jordanian financial market that prevent to applied option market. It requires from government authority to provide suitable invested environment to apply option market on Jordan.